Regulation of gambling in Sub-Saharan Africa: findings from a comparative policy analysis. (January 2023) - Sichali, J.M.; Bunn, C.; McGee, D.; Marionneau, V.K.; Yendork, J.S.; Glozah, F.; Udedi, M.; Reith, G.
Abstract: Objectives: Commercial gambling markets have undergone unprecedented expansion and diversification in territories across Sub-Saharan Africa (SSA). This gambling boom has popularised the uptake of gambling products in existing circuits of popular culture, sport and leisure and raised concerns about the extent to which state legislation is equipped to regulate the differentiated impacts of gambling on public health. Study design: Comparative policy analysis. Methods: This article provides a systematic mapping of the regulatory environment pertaining to gambling across SSA. The review was conducted by obtaining and triangulating data from a desk review of online materials, consultation with regulatory bodies in each territory and the VIXIO Gambling Compliance database. Results: Gambling is legally regulated in 41 of 49 (83.6%) SSA countries, prohibited in 7 (14.3%) and is not legislated for in 1 (2.0%). Of those countries that regulate gambling, 25 (61.0%) countries had dedicated regulators and 16 (39.0%) countries regulated via a government department. Only 2 of 41 (4.9%) countries have published annual reports continuously since the formation of regulatory bodies, and 3 (7.3%) countries have published an incomplete series of reports since the formation. In 36 (87.8%) countries, no reports were published. Enforcement activities were documented by all five regulators that published reports. Conclusion: The review uncovered a lack of coherence in regulatory measures and the need for more transparent public reporting across SSA territories. There are also variations in regulating online products and marketing, with most countries lacking apt guidelines for the digital age. Our findings suggest an urgent need to address the regulatory void surrounding online forms of gambling and the promotion of gambling products. This underlines the importance of a public health approach to protect against an increase in gambling-related harms.